2008
DOI: 10.1007/s10533-008-9217-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition of organic matter in sandy relict and cultivated heathlands as examined by pyrolysis-field ionization MS

Abstract: Unusually high SOC levels have been reported for sandy cropland soils in North-Western Europe. A potential link with their general heathland land-use history was investigated by comparing two soil pairs of relict heathland and cultivated former heathland in the Belgian sandy region. A sequential chemical fractionation yielded similar sizes in corresponding SOM fractions between the heathland and cropland soils (i.e. NaOCl resistant: 12.3-15.0 g C kg(-1) and NaOCl + HF resistant: 2.6-5.3 g C kg(-1)). Higher amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
(70 reference statements)
0
33
1
Order By: Relevance
“…2). Compared to the TOC concentrations of sandy long-term cropland soils from many regions of Northwest Europe, which have been reported to exhibit about 20 g kg −1 TOC (Sleutel et al 2008;Springob et al 2001;Strebel et al 1988), the TOC concentrations of the soils of this study, which have been used as cropland for 46 years, are very low. Probably, the reason for the high TOC contents in other sandy long-term cropland soils is a former use of the sites as heathland and the input of recalcitrant Callunaderived organic matter (Sleutel et al 2008;Springob and Kirchmann 2003).…”
Section: Toc Land Use and Land Use Changecontrasting
confidence: 62%
See 1 more Smart Citation
“…2). Compared to the TOC concentrations of sandy long-term cropland soils from many regions of Northwest Europe, which have been reported to exhibit about 20 g kg −1 TOC (Sleutel et al 2008;Springob et al 2001;Strebel et al 1988), the TOC concentrations of the soils of this study, which have been used as cropland for 46 years, are very low. Probably, the reason for the high TOC contents in other sandy long-term cropland soils is a former use of the sites as heathland and the input of recalcitrant Callunaderived organic matter (Sleutel et al 2008;Springob and Kirchmann 2003).…”
Section: Toc Land Use and Land Use Changecontrasting
confidence: 62%
“…The NaOCl-resistant C fraction in this study represented 8 to 53% of the initial TOC concentration for the chronosequence sites. Sleutel et al (2008) found that the NaOCl-resistant C fraction of sandy soils with recent or historical heathland use ranged between 49 and 78% of the TOC. This significant difference shows that the soil organic matter of the Gleyic Podzols and Haplic Gleysols under cropland is more labile than that of the sites investigated by Sleutel et al (2008).…”
Section: Chemical Oxidation Resistant C Toc and Land Usementioning
confidence: 99%
“…As discussed by Sleutel et al (2008), because of the low content of both crystalline and poorly crystalline Fe and Al (Tab. 1), binding between the latter and SOM plays only a limited role in SOM stabilization in these soils.…”
Section: Discussionmentioning
confidence: 96%
“…Calluna litter contains very stable SOC due to high contents of lipids, 397 long-chain aliphatics and sterols, and may persist in the light fraction of soil for decades or even 398 centuries (Sleutel et al, 2008). 399…”
Section: Black Sands 388mentioning
confidence: 99%